Pengaruh Prinsip Kepenggunaan Islam dan Dimensi Maqasid Daruriyyah dalam Inovasi Produk Halal di Malaysia: The Influence of Islamic Consumerism Principles and the Maqasid Daruriyyah Framework on Halal Product Innovation in Malaysia - Omar, N.,; Abdul Aziz, S.,; Mahaiyadin, M. H.,; Zainuzzaman, A. K.,; Muda, Z., (Global Journal Al-Thaqafah, 2024)
In line with the rapid economic progress, the halal food industry and products have become catalysts in boosting the country's economic power. There is a significant and increasing demand for halalan tayyiban food products over time, not only to meet the needs of Islamic countries but also non-Islamic nations. The sophistication of food products resulting from modern innovation and technology has sparked debates and controversies regarding their compliance with Islamic consumer principles. Therefore, this study aims to identify the dominant principles of Islamic consumerism to address emerging issues, with an emphasis on the Maqasid Daruriyyah dimensions proposed by both classical and contemporary Islamic scholars. The study employs a qualitative approach through documentation methods and semi-structured interviews. The findings highlight four dominant principles in contemporary Islamic consumerism for the halal food industry and products: Halal; Tayyib; Shariah-Compliant Innovation; and the Islamic Ecosystem. A new dimension of Maqasid Daruriyyah is also introduced as a means of mediating these issues. This study serves as a reference and guide for various authorities and stakeholders in addressing the challenges of consumerism related to innovative food products. The principles of Islamic consumerism are crucial to ensure full compliance with Shariah in navigating the rapid advancements in halal product innovation.